Utilization of Oil Palm Leaf Rib Waste (Elaeis guineensis) as Material for Making Handicrafts in Aek Batu Village - Ilham Hakiki Harahap; Nurlina Ariani; Amin Harahap; Adila Saftri; Rindiani Rindiani (CV. AFDIFAL MAJU BERKAH, 2026)
This community outreach activity was carried out with the aim of helping residents of Aek Batu Village, Torgamba District, South Labuhanbatu Regency, utilize palm oil (Elaeis guineensis) palm frond waste into innovative handicrafts that have sales value. The product from palm oil (Elaeis guineensis) palm frond waste is a handicraft in the form of a Peacock Replica